2022
DOI: 10.3389/fpsyg.2022.945631
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between social exclusion and smartphone addiction: The mediating roles of loneliness and self-control

Abstract: Previous studies have identified many antecedents of smartphone addiction. However, social exclusion as a risk factor for smartphone addiction has not been widely studied, and little is known concerning the psychological mechanism underlying this association. The present study tested the influence of social exclusion on smartphone addiction as well as the mediating roles of loneliness and self-control in this relationship. An online survey was conducted, and the sample consisted of 573 university students (323… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 72 publications
3
11
0
Order By: Relevance
“…This study also found that self-control can signi cantly mediate between social exclusion and short video addiction, which veri ed hypothesis 3. For the rst path of this indirect effect, social exclusion can substantially weaken the self-control ability, consistent with the previous research results [37] and in line with the view of the temporal need-threat model [16].…”
Section: The Mediating Role Of Self-controlsupporting
confidence: 91%
See 1 more Smart Citation
“…This study also found that self-control can signi cantly mediate between social exclusion and short video addiction, which veri ed hypothesis 3. For the rst path of this indirect effect, social exclusion can substantially weaken the self-control ability, consistent with the previous research results [37] and in line with the view of the temporal need-threat model [16].…”
Section: The Mediating Role Of Self-controlsupporting
confidence: 91%
“…In addition, such people will also experience a sense of powerlessness and helplessness in coping with the event, resulting in a decline in their level of self-control [17]. Moreover, social exclusion can also lead to rumination, thus occupying cognitive resources and reducing the ability for individual self-control [37]. For the second path of this indirect effect, self-control can signi cantly negatively predict short video addiction, which is consistent with the results of previous similar studies [22,23].…”
Section: The Mediating Role Of Self-controlmentioning
confidence: 99%
“… 6 , 52 When individuals are unable to establish and maintenance satisfying interpersonal relationships in real life, they may turn to smartphones, a widely used tool for consuming time and easing negative emotions including loneliness and seeking immediate relief from negative emotions temporarily. 53 , 84 , 85 Moreover, lonely individuals tend to exhibit incompetence in social relationships, and they are less willing to communicate with others face to face. In contrast, they are more eager to establish supportive interpersonal relationships through virtual smartphones, a substitute for interpersonal communication.…”
Section: Discussionmentioning
confidence: 99%
“…When adolescents are suffering from loneliness, smartphones are used as an available approach for them to escape the feeling of loneliness and related negative experiences and also help them feel relaxed, thereby stimulating their motivations to indulge in smartphones more frequently and resulting in smartphone addiction. 6 , 52 , 53 Adolescents who are experiencing loneliness prefer to surf the Internet, play games, or attend online interactions instead of face-to-face communication to release this negative feeling or improve their belonging and relationship needs, 54 , 55 thus further exacerbating the risk of smartphone addiction. 42 , 56 , 57 Moreover, those who suffer from loneliness are more likely to develop negative perceptions and be dissatisfied with real life, which motivate them to turn to the virtual world (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cronbach’s alpha for the scale across the whole group was 0.883, with 0.895 and 0.872 for male for female participants, respectively. The construct validity of SAS-SV has been verified in various cultures and countries [ 23 , 25 31 ], and it is correlated with numerous measures [ 52 , 53 ], thus providing convergent and concurrent construct evidence for the validity of this scale.…”
Section: Methodsmentioning
confidence: 99%